Late Etkin. (Revista Argentina de Musicología, 2014)
This article deals with the music of the Argentinian composer Mariano Etkin (Buenos Aires, 1943), one of the most original figures in the Latin American musical scene of the past thirty years. The approach to his music and to his significant theoretical production, could not but be selective. Our goal is to describe the passage from the textural to the melodic-linear dimension in Etkin’s music, while also trying to explain how the “textural” philosophy of the 80s survives in the composer’s late style. This paper, which revolves not only around music but also around ideology, affirms that from the noteto- note microvariatons in Caminos de cornisa (1985) to the random variations piece-topiece in Estudios para lágrimas I and II (2009-2011), Etkin has ended up pulverizing all evidence of an aesthetic-identitary program. Of course, the development of his music would be unthinkable without his personal elaboration of those earlier starting points.
Keywords: Mariano Etkin; late style; texture; melodic-linear